Audience Reception of Hoax Information on Social Media in the Post-Truth Era - Wahyono, Sugeng Bayu; Wirasti, Murti Kusuma; Ratmono, Barito Mulyo (UI Scholars Hub, 2020)
This research is an audience reception study of hoax information on social media during the 2019 Presidential Election campaign in the post-truth era. This research uses a qualitative method with a reception study approach and various theories of active audiences such as the encoding-decoding model from Stuart Hall, which was also elaborated by David Morley and Ien Ang. The result shows that there are three typologies in receiving hoax. Those are the pragmatic-creative, ideological, and critical-skeptical type of audiences. The three typologies of the audience have different characters in the reception of hoax information in political communication on social media. Some audiences are permissive-negotious, some are critically oppositional, and some are hegemonized by hoax information in the 2019 Presidential Election political moment in such a way that they are part of the increasing turbulence of hoax. Penelitian ini merupakan studi resepsi khalayak terhadap informasi hoaks di media sosial pada masa kampanye Pilihan Presiden 2019 dalam era pascakebenaran. Riset ini menggunakan metode kualitatif dengan pendekatan studi resepsi, dan menggunakan berbagai teori khalayak aktif seperti model encoding-decoding dari Stuart Hall yang dielaborasi juga oleh David Morley dan Ien Ang. Hasil penelitian menunjukkan bahwa terdapat tiga tipologi khalayak dalam menerima hoaks, yaitu khalayak tipe pragmatik-rekreatif, ideologis, dan kritis-skeptis. Ketiga tipologi khalayak itu memiliki karakter yang berbeda dalam meresepsi informasi hoaks dalam komunikasi politik di media sosial. Ada yang permisif-negosiatif, ada yang kritis oposisional, dan ada pula yang terhegemoni oleh informasi hoaks dalam momen politik Pilihan Presiden 2019, sehingga menjadi bagian dari peningkatan turbulensi hoaks.